2017
DOI: 10.1111/1348-0421.12490
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma bovis isolates from dairy calves in Japan have less susceptibility than a reference strain to all approved macrolides associated with a point mutation (G748A) combined with multiple species‐specific nucleotide alterations in 23S rRNA

Abstract: Erythromycin, tylosin and tilmicosin are approved for use in cattle in Japan, the latter two being used to treat Mycoplasma bovis infection. In this study, 58 M. bovis isolates obtained from Japanese dairy calves all exhibited reduced susceptibility to these macrolides, this widespread reduced susceptibility being attributable to a few dominant lineages. All 58 isolates contained the G748A variant in both the rrl3 and rrl4 alleles of 23S rRNA, whereas a reference strain (PG45) did not. G748 localizes in the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…All non-WT isolates for the 16-membered-ring macrolide TIL contained the G748A mutation in domain II of both 23S rRNA alleles, which was also observed in previous studies ( 15 , 19 , 29 , 36 ). An additional mutation at position 2058 was associated with GAM (15-membered ring) and TYL (16-membered-ring) resistance in our GWAS.…”
Section: Discussionsupporting
confidence: 83%
“…All non-WT isolates for the 16-membered-ring macrolide TIL contained the G748A mutation in domain II of both 23S rRNA alleles, which was also observed in previous studies ( 15 , 19 , 29 , 36 ). An additional mutation at position 2058 was associated with GAM (15-membered ring) and TYL (16-membered-ring) resistance in our GWAS.…”
Section: Discussionsupporting
confidence: 83%
“…This failure of antimicrobial therapy might also suggest the presence of more than one pathogen that was responsible for the unresponsive treatment [8,19-22]. Furthermore, in vitro studies in Europe have reported high minimum inhibitory concentrations against circulating M. bovis for many of the commercially available antimicrobials [21].…”
Section: Discussionmentioning
confidence: 99%
“…Biased sampling might therefore result from using Vigimyc strains as they often originate from antimicrobials-treated animals. Mycoplasma species are known to evolve fast, and they develop AMR mainly through mutations in antimicrobial targets, which could be rapidly selected under antimicrobial pressure [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%